A hair and hair vortex simulation technique based on vector fields on a manifold - Huan, Nguyen Van (Vietnam Journal of Science and Technology, 2016)
Hair is an important component in the virtual human simulation system. During hair simulation, not only the time required to ensure that there are required to express the physical characteristics, chemical such as hair styles, colors, curves, twists, parting one’s hair and hair vortex (swirl), ... to represent the authenticity of the hair and improve hair simulation quality. While the studies has announced today that they mainly focus on simulating the styles, the motion of the hair that has not been expressed characteristics of hair as hair vortex,... The paper introduces the concept of scalp model as a manifold in 3-dimensional space. Based on the nature of the singularity of the vector field on the manifold, the paper proposes a hair simulation technique on the scalp surface model based on vector field on the manifold. Thus, we can simulate appropriately the hair vortex on the scalp model.